Dendrochronology of Ancient Pine Trunks Exposed at the Coastal Bluff: Dating Problems and Possible Causes - Zunde, Māris (Frontiers in Ecology and Evolution, 2022)
Coastal erosion and slumping of the coastal bluff occur at the present day along certain stretches of the Baltic Sea coastal belt in western Latvia. The coast currently being eroded is regarded as consisting partly of a cover of wind-blown sand formed 250–300 years ago, a period that saw intensive landward aeolian sand transport as a result of forest cutting and forest fires in the coastal belt and other factors relating to human activity. Within the frame of a short-term research project, dendrochronological dating work was undertaken on remnants of pine trunks discovered at various locations on the coastal bluff that appeared to be remains of ancient trees exposed by erosion, with the aim of determining where and when these natural processes had occurred. This study did not succeed in demonstrating dendrochronologically that the apparently ancient tree trunk remnants observable along certain stretches of the coast at the present day are remains of pines buried by sand more than 250 years ago. It has been established that certain of these are remnants of pines that died in the 20th century or even just a few years ago, but in the majority of cases an unambiguous old date could not be obtained. In order to ascertain the possible reasons why dendro-dating had produced such limited results, in the further part of the study a comparison was undertaken of the patterns of variation in annual radial trunk growth of pines growing in the dune belt along the whole of the Latvian seaboard at the present day. Also considered are the previous findings of short-term studies in all three Baltic States concerning the influence of specific environmental factors on the radial growth of pine. It has been established that the reasons why dendro-dating was problematic relate to the specific character and variation in the environmental factors significantly affecting tree growth, as well as the slope processes on the coastal bluffs. It is envisaged that the findings obtained and brought together in this study will be useful in future, when undertaking or planning dendro-dating work for the purpose of tracing the history of dune migration or assessing the radial growth of pines growing in dunes.